A Step-by-Step Protocol for Optogenetic Kindling - Cela, Elvis; Sjöström, P. Jesper (Frontiers in Neural Circuits, 2020)
Electrical kindling, repeated brain stimulation eventually resulting in seizures, is widely used as an animal model of epileptogenesis and epilepsy. However, the stimulation electrode used for electric kindling targets unknown neuronal populations and may introduce tissue damage and inflammation. Optogenetics can be used to circumvent these shortcomings by permitting millisecond control of activity in genetically defined neurons without gross injury or inflammation. Here we describe an easy step-by-step protocol for optogenetic kindling – optokindling – by which seizures are eventually elicited in initially healthy mice through repeated light stimulation of neurons expressing Channelrhodopsin-2 (ChR2). Chronic EEG recordings may be performed over large time scales to monitor activity while video camera monitoring may be used to assess the behavioral severity of seizures. In conclusion, with optokindling, neuroscientists can elucidate the circuit changes that underpin epilepsy while minimizing the contribution of confounding factors such as brain damage and inflammation.